ANTI-DRUG AMBASSADORS AS NON-FORMAL EDUCATION AGENTS: A STUDY OF ROLES AND STRATEGIES IN DRUG PREVENTION IN SAMARINDA - Awaliyah Rahman; Sri Wahyuni; Hepy Triwinarti; Wahdatan Nisa (SOSIOEDUKASI, 2025)
Drug abuse among adolescents is a serious problem that requires an effective prevention approach. The Anti-Drug Ambassador Program as a non-formal education agent is present as an innovative strategy in increasing public awareness, especially the younger generation in Samarinda. This study aims to analyze the role, strategies and challenges of Anti-Drug Ambassadors in efforts to prevent drug prevention through peer-education-based non-formal education . This study uses a phenomenological qualitative approach, and data collection techniques used in-depth interview techniques, participatory observation, and documentation studies. In this study, the data analysis technique is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that: (1) Anti-Drug Ambassadors have an important role as peer educators, non-formal education agents, community facilitators, anti-drug advocates, and agents of change. (2) The strategies used include persuasive communication, community-based approaches, collaboration with community leaders, interactive counseling, and the use of digital media. (3) The Anti-Drug Ambassador Program still faces challenges such as limited funds, weak member commitment, and lack of budget support from local governments. Overall, the Anti-Drug Ambassador Program in Samarinda has proven to be effective in shaping the resilience of young people to harm through relevant and contextual non-formal education methods.